Musculoskeletal fitness: relative handgrip strength and vertical jump power from 10 to 18 years old - Correia, Abel S.; Zymbal, Vera; Baptista, Fátima (Frontiers in Pediatrics, 2024)
Background There is an increasing consensus on the relevance of musculoskeletal fitness for health throughout the life cycle, requiring evaluation approaches and description of results capable of characterizing different age groups and body sizes. This study aimed to describe the musculoskeletal fitness of young Portuguese people aged 10–18 through handgrip strength (HGS) and vertical jump power (VJP) and investigate differences between the sexes. Methods The sample included 736 participants (359 girls recruited from schools. HGS (kg) was assessed using a handheld dynamometer, and VJP (W) was assessed using a force platform; both measurements were standardized for body mass. Results Higher HGS and VJP were observed in boys than in girls from 13 years old (13 years: p ≤ 0.05; 14–18 years: p ≤ 0.001), with no significant differences before this age. The percentile distributions of HGS and VJP are described for each sex using the lambda, mu, sigma (LMS) method. The pattern of development of these variables as a function of age is presented. Conclusions Handgrip strength and vertical jump power show differences between the sexes from 13 years of age and similar trajectories to populations in other countries in the same age group.